Neuroscience Contribution in Educational Leadership. Challenges and Perspectives - Stiliadi, Stella (Technium Education and Humanities, 2024)
Education is founded upon the instruction process and its outcomes, commonly called learning outcomes. The underlying foundation of this entire process is the brain. Neuroscience encompasses the study of brain function, including the intricate processes involved in human learning. It also investigates the factors that contribute to variations in learning abilities among individuals. Therefore, it is unsurprising that individuals engaged in educational science are highly interested in integrating the discoveries of neurosciences with educational theories of learning. Neuroscientific research has been conducted for approximately three decades. However, there has been a growing interest in integrating neuroscience and education in recent years. This is evident from the numerous articles published in books and scientific journals that explore the relationship between these two fields. Additionally, the integration of neuroscience into educational leadership presents both opportunities and challenges. Educational neuroscience posits that insights from neuroscience can enhance teaching in the classroom. However, there are practical and principled issues associated with educational neuroscience, which need to be addressed. Neuroscience is revealing to educational leadership that it is a social process, with the human brain being a social organ interacting with others in social contexts. Incorporating neuroscience into educational leadership has the potential to increase its effectiveness, but contradictory studies address the critical nature of this integration. The application of advances in psychology, behavioral economics, and cognitive neuroscience to study school leaders’ decision-making processes is a tantalizing area. Finally, it is essential that neuroscientific data and interpretations are rooted in education to be embraced by the education profession.